High adherence to adjuvant endocrine therapy improves outcome in early breast cancer: results from a large real-world claims data analysis in Germany = Eine hohe Adhärenz zur adjuvanten endokrinen Therapie verbessert das Outcome bei frühem Brustkrebs : Ergebnisse aus einer großen Real-World-Datenanalyse in Deutschland - Dannehl, Dominik; Dijkstra, Tjeerd; Volmer, Lea; Hahn, Markus; Au, Alexandra von; Hawighorst-Knapstein, Sabine; Chaudhuri, Ariane; Wallwiener, Markus; Bauer, Armin; Wallwiener, Diethelm; Brucker, Sara; Wallwiener, Stephanie; et al. (Geburtshilfe und Frauenheilkunde, 2026)
In hormone-receptor positive (HR+) early breast cancer (EBC), adjuvant endocrine therapy (ET) significantly reduces recurrence and mortality. A common means of estimating therapy adherence is to use patient-reported outcome measures. Yet, this method is inaccurate due to social-desirability bias. We therefore aimed to analyze adherence to ET over the first five years of treatment by using claims data from a large health insurance provider in Germany (AOK Baden-Wuerttemberg). Female patients diagnosed with HR+ EBC who received inpatient treatment and breast cancer surgery between 1 July 2010 and 31 December 2019 were included in the analysis. Adherence to ET was defined as the ratio between the sum of the number of pills from filled prescriptions and the duration of ET in days (from the start of the first prescription after completing surgery and chemotherapy). ET use was observed over five years. Low adherence was defined as a ratio smaller than 0.8 and high adherence as a ratio larger than or equal to 0.8. Distant recurrence-free survival (DRFS) was calculated from the day of the first diagnosis of EBC until onset of distant recurrence. Overall survival (OS) was defined as the period between first diagnosis of EBC until death of any cause. In total, 16642 patients with EBC were included. Of these patients, 4303 (86%) showed high adherence to ET in the first year after initiating treatment. After five years, high adherence persisted in 68% of patients. Continuous high adherence to ET had a significant impact on DRFS (HR: 0.66; 95% CI: 0.58-0.76, p > 0.0001) and OS (HR 0.52, 95% CI: 0.47-0.57, p < 0.0001). In conclusion, adherence to ET is an independent risk factor that significantly influences DRFS and OS. Further real-world studies should explore the factors contributing to treatment discontinuation and evaluate prospective strategies to enhance adherence.
Online veröffentlicht: 10.9.2025
Gesehen am 23.01.2026